AHP-based analysis of the risk potential of safety incidents: Case study of cranes in the construction industry. (January 2017) - Raviv, Gabriel; Shapira, Aviad; Fishbain, Barak
Highlights: The AHP method was applied to evaluate safety incident outcome severity. Expert knowledge was elicited to understand cost versus company reputation damages. Total risk potential was introduced and measured in relation to a given database. A tool for the quantitative evaluation of multi-incident reports was introduced. Abstract: The use of data collected from near-miss reports has added value to safety in high-hazard industries such as aviation and the process industry, but this procedure has not yet taken root in construction management practice. Although the management of near-miss reporting systems and the collection of near-miss event reports have been the focus of recent research efforts, the structural analyses of reports have not yet been investigated. This paper reports on a multi-phase research that studied near misses related to crane work and their safety risk potential. Former research stages concentrated on collecting near-miss as well as accident stories and established a structured database of tower-crane related events. The reported events were further classified into five homogeneous clusters and their potential for escalating into accidents at a given outcome severity level was assessed. The research stage reported in this paper builds on the results of the previous stage results, and implements the analytic hierarchy process (AHP) to evaluate the quantitative outcome severity level values, thus computing each event's total risk potential. The research outcomes reveal inter-relations between technical factors and human factors in the tower-crane domain. Further application is demonstrated, using the risk potential values for construction company safety assessments.